Category of fuzzy topographic topological mapping (FTTM) - Faisal Abdurabu Mubarak Binjadhnan, 1975- 276199; Tahir Ahmad, supervisor; Fakulti Sains 8004 (2007)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2007